2017
DOI: 10.1016/j.watres.2017.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freshwater sediment characteristics on the persistence of fecal indicator bacteria and genetic markers within a Southern California watershed

Abstract: In this study, the aging of culturable FIB and DNA representing genetic markers for Enterococcus spp. (ENT1A), general Bacteroides (GB3), and human-associated Bacteroides (HF183) in freshwater sediments was evaluated. Freshwater sediment was collected from four different sites within the upper and lower reach of the Topanga Creek Watershed and two additional comparator sites within the Santa Monica Bay, for a total of six sites. Untreated (ambient) and oven-dried (reduced microbiota) sediment was inoculated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Several studies reported increased E. coli persistence after addition of organic carbon in the form of fecal material (88,89) or organic-rich sediment (81) ( Table 1). FIB decay rates were often reduced in sediment compared to the overlying water column (81,88), and culturable E. coli and enterococci, as well as the GenBac3 MST marker, decayed more slowly in sediments with higher organic carbon levels (94). Extended survival in sediments is attributed to factors including greater access to nutrients, such as organic carbon, and protection from UV light and predators.…”
Section: Nutrientsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies reported increased E. coli persistence after addition of organic carbon in the form of fecal material (88,89) or organic-rich sediment (81) ( Table 1). FIB decay rates were often reduced in sediment compared to the overlying water column (81,88), and culturable E. coli and enterococci, as well as the GenBac3 MST marker, decayed more slowly in sediments with higher organic carbon levels (94). Extended survival in sediments is attributed to factors including greater access to nutrients, such as organic carbon, and protection from UV light and predators.…”
Section: Nutrientsmentioning
confidence: 99%
“…Extended survival in sediments is attributed to factors including greater access to nutrients, such as organic carbon, and protection from UV light and predators. Other factors, such as sediment properties (e.g., particle size and clay content), as well as the presence of biofilms, can also promote extended survival in sediment (81,88,94).…”
Section: Nutrientsmentioning
confidence: 99%
See 2 more Smart Citations
“…After deposition onto stream waters, fecal bacteria often become incorporated in stream sediments (Droppo et al, 2009), where they have been shown to survive for several weeks (Haller et al, 2009; Martín‐Díaz et al, 2017). Therefore, stream sediments can function as fecal contamination reservoirs, acting not only as sinks but also as sources of fecal contamination (Agouridis et al, 2005) when inevitable disturbance events take place (Nagels et al, 2002; Ekwanzala et al, 2017; Zimmer‐Faust et al, 2017), such as cattle drinking or crossing the streams or high rainfall events. For instance, Craig et al (2004), at a recreational coastal site in Australia, observed a dramatic increase of fecal coliforms concentrations in both waters and sediments from 17 ± 11 CFU 100 mL −1 and 143 ± 57 CFU 100 mg −1 to >10 6 CFU 100 mL −1 and 10 6 CFU mg −1 , respectively, after a significant rainfall event.…”
Section: In‐stream and Sediment Pathogenic Microbesmentioning
confidence: 99%